2006
DOI: 10.1007/s11604-006-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical evaluation of calibration curve for diagnostic LCD monitor

Abstract: Purpose. In 1998, Digital Imaging Communications in Medicine (DICOM) proposed a calibration tool, the grayscale standard display function (GSDF), to obtain output consistency of radiographs. To our knowledge, there have been no previous reports of investigating the relation between perceptual linearity and detectability on a calibration curve. Materials and methods. To determine a suitable calibration curve for diagnostic liquid crystal display (LCD) monitors, the GSDF and Commission Internationale de l'Eclair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the initial image is no longer relevant. Other studies have concluded that CIE calibration is a better calibration method, 25 but we were interested in the GSDF of DICOM because DICOM is the gold standard in radiology. In this study, the DICOM calibration was achieved using LUTs incorporated into the viewing software, which produce quantization errors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the initial image is no longer relevant. Other studies have concluded that CIE calibration is a better calibration method, 25 but we were interested in the GSDF of DICOM because DICOM is the gold standard in radiology. In this study, the DICOM calibration was achieved using LUTs incorporated into the viewing software, which produce quantization errors.…”
Section: Resultsmentioning
confidence: 99%
“…We must investigate the optimal viewing size for detecting n-GGOs from the viewpoint of the human visual system in the future. Third, other factors were not evaluated such as the display luminance and display function, which also influence observer performance [20][21][22][23]; however, GSDF is recommended as a standard display function for soft-copy diagnosis [24]. Fourth, we did not use a low-dose protocol for lung cancer CT screening.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a new grayscale test pattern (NGTP) was developed to adjust the gradient of gray levels in thoracic computed tomography (CT) images [12] . The pattern has also been applied to the psychophysical evaluation of display functions for LCD monitors [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%